Low-carbon high-strength building regenerated micro-powder compounded red mud cementing material and preparation method thereof

Through the preparation method of low-carbon and high-strength building recycled micro powder combined with red mud gelling materials, ultrafine red mud powder and building recycled micro powder are prepared by gas phase milling, and stirred with reinforcement, the problem of large-scale low-carbon utilization of fine aggregates of waste concrete and red mud is solved, and low-carbon production and high-strength performance gelling materials are achieved.

CN119613074APending Publication Date: 2025-03-14GUANGXI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411582805.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing technology has failed to effectively solve the problem of the utilization of fine aggregates of waste concrete in construction and the large-scale low-carbon utilization of red mud. The current development direction of building materials is high strength and durability, but there is a cement firing industry with high energy consumption and high pollution, which is difficult to meet the low-carbon development goals.

Method used

Low-carbon and high-strength building recycled micro powder is used to combine red mud gelling materials, and ultrafine red mud powder and building recycled micro powder are prepared by gas phase grinding, and evenly stirred with the reinforcement to form a gelling material with low-carbon production and high-strength performance.

Benefits of technology

It has realized the coordinated regulation and comprehensive utilization of building recycled micro powder and red mud, effectively replaced cement cementitious materials, and has the characteristics of low-carbon production and high-strength performance, solving the dual problems of solid waste resource utilization and low-carbon development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of solid waste resource utilization research, in particular to a low-carbon and high-strength building regenerated micro powder compounded red mud cementing material and a preparation method thereof.The low-carbon and high-strength building regenerated micro powder compounded red mud cementing material is prepared from, by mass, 40-70 parts of superfine red mud powder, 30-60 parts of building regenerated micro powder and 5-10 parts of a reinforcing agent; the building regenerated micro powder comprises regenerated mortar powder and / or regenerated red brick powder, the reinforcing agent comprises a super plasticizer, a penetrating agent and an activating agent, and the superfine red mud powder, the building regenerated micro powder and the reinforcing agent are subjected to gas-phase grinding and stirring according to the proportion to obtain the material. The low-carbon high-strength building regenerated micro-powder compounded red mud cementing material can not be subjected to a high-temperature calcination process, the strength grade is not lower than 42.5 MPa, low-carbon preparation of an inorganic cementing material can be achieved, a large amount of solid waste materials such as red mud and building waste are utilized, and therefore the purposes of energy conservation, emission reduction and solid waste resource utilization are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the research field of solid waste resource utilization, and specifically is a low-carbon high-strength building recycled micropowder compounded red mud cementitious material and a preparation method thereof. Background Art

[0002] Urbanization and industrialization are the two most important processes in the world today. In the process of urban renewal and development, a large amount of construction solid waste materials such as discarded concrete are generated. In the process of industrial production, industrial solid waste represented by red mud and other waste materials are also generated. According to statistics, the historical cumulative stockpile of industrial solid waste in my country is as high as 62 billion tons, and the annual increase in stockpile is nearly 3.5 billion tons. Therefore, how to efficiently utilize and dispose of construction solid waste and industrial solid waste is extremely important.

[0003] At present, domestic and foreign researchers mostly crush construction waste concrete to obtain coarse aggregate, strengthen it through physical and chemical modification methods, and then add it to concrete to replace part of the natural aggregate. However, fine aggregate is generally landfilled and has not been effectively applied; for red mud industrial solid waste materials, it is currently mainly stored, occupying a large amount of land resources, and the discharge of high-alkali wastewater will pollute the surrounding water sources. Although the application of red mud has been proposed, such as adding it to cement clinker for firing together to obtain high-aluminum cement, cement firing is a high-energy consumption and high-pollution industry, which does not meet the current national goals.

[0004] The resource utilization of construction waste concrete and red mud is a significant problem. The existing technology has not yet solved the problem of the utilization of fine aggregate of construction waste concrete and the large-scale low-carbon utilization of red mud. In addition, current building materials are developing towards high strength and durability. Therefore, there is an urgent need to find a low-carbon and high-strength method for the coordinated regulation and utilization of construction recycled micropowder and red mud. Summary of the invention

[0005] Based on the problems existing in the prior art, the present invention proposes a low-carbon and high-strength building recycled micropowder compounded with red mud cementitious material and a preparation method thereof, which can realize the coordinated regulation and comprehensive utilization of building recycled micropowder and red mud, achieve the purpose of solid waste resource utilization, and effectively replace cement cementitious materials. It has the characteristics of low-carbon production and high-strength performance, and is adapted to the current trend of technological development.

[0006] The technical solution adopted by the present invention is:

[0007] A low-carbon high-strength building recycled micropowder compounded red mud cementitious material, comprising the following components in parts by mass:

[0008] Ultrafine red mud powder: 40-70 parts;

[0009] Building recycled micro powder: 30-60 parts;

[0010] Enhancer: 5-10 parts;

[0011] The ultrafine red mud powder and the building recycled micro powder are gas-phase ground, and the mixture is evenly stirred with a reinforcing agent to obtain a low-carbon and high-strength building recycled micro powder-compounded red mud cementitious material.

[0012] Furthermore, the ultrafine red mud powder is composed of graded nano powder, and the pass rate and mass fraction of each particle size are as follows:

[0013] 100 mesh-200 mesh: 90%-100%;

[0014] 200 mesh-500 mesh: 70%-80%;

[0015] 500 mesh-1000 mesh: 50%-70%;

[0016] 1000 mesh-3000 mesh: 30%-50%;

[0017] 3000 mesh-5000 mesh: 10%-30%.

[0018] Furthermore, the construction recycled micro powder is one or a combination of recycled mortar powder and recycled red brick powder; the fineness of the construction recycled micro powder meets the requirement of 0.075mm with a pass rate of more than 90%.

[0019] Furthermore, the mass fraction of CaO in the building recycled fine powder is greater than 25%, the mass fraction of SiO2 is greater than 30%, and the mass fraction of Al2O3 is greater than 20%.

[0020] Furthermore, the reinforcing agent comprises a superplasticizer, a penetrant and an activator, and the mass fractions thereof are as follows:

[0021] Superplasticizer: 2-5 parts;

[0022] Penetrant: 1-3 parts;

[0023] Activator: 1-5 parts.

[0024] Furthermore, the superplasticizer is one or more of polycarboxylates, aminosulfonates, and acrylic resins.

[0025] Furthermore, the penetrant is one or more of silicate, calcium chloride, and nano-magnesium fluorosilicate.

[0026] Furthermore, the activator is one or more of nano sodium silicate, nano sodium hydroxide, and calcium oxide.

[0027] The present invention also provides a method for preparing the low-carbon high-strength building recycled micropowder compounded red mud cementitious material, comprising the following steps:

[0028] S1. Dry the red mud and construction solid waste separately, and the water content is required to be no more than 0.2wt%;

[0029] S2. Preparation of ultrafine red mud powder: Grinding red mud with a gas colloid mill, preparing graded nanopowders with particle size pass rates and mass fractions of 100 mesh-200 mesh: 90%-100%, 200 mesh-500 mesh: 70%-80%, 500 mesh-1000 mesh: 50%-70%, 1000 mesh-3000 mesh: 30%-50%, 3000 mesh-5000 mesh: 10%-30% respectively according to the grinding time;

[0030] S3. Preparation of recycled building powder: Grinding construction solid waste by gas colloid mill to obtain recycled mortar powder and / or recycled red brick powder with a pass rate of more than 90% at 0.075mm;

[0031] S4. Preparation of enhancer: 2-5 parts of superplasticizer, 1-3 parts of penetrant and 2-5 parts of activator are simultaneously added to a mixing tank and stirred for 5-8 minutes at a stirring rate of 100-200 rpm;

[0032] S5. Preparation of low-carbon and high-strength building recycled micropowder compounded red mud cementitious material: first mix 40-70 parts of ultrafine red mud powder with 5-10 parts of reinforcing agent, stir in a mixing pot for 5-10 minutes, then add 30-60 parts of building recycled micropowder, stir for 5-10 minutes, and you can get a uniform low-carbon and high-strength building recycled micropowder compounded red mud cementitious material.

[0033] The beneficial effects of the present invention include:

[0034] (1) The method for preparing a low-carbon, high-strength building recycled micropowder compounded red mud cementitious material of the present invention is a low-carbon method for producing cementitious materials, which does not require high-temperature calcination. A high-strength cementitious material can be obtained by simply mixing ultrafine red mud powder, building recycled micropowder and a reinforcing agent. The preparation method is simple and feasible, and the production process is low-carbon and environmentally friendly, which is in line with the current national strategic goal of low-carbon development;

[0035] (2) It can effectively replace cement binder materials and has high strength characteristics, with a 28-day compressive strength of no less than 50 MPa;

[0036] (3) It effectively solved the problem of large-scale utilization of recycled micropowder from construction solid waste and red mud from industrial solid waste, solved the problem of large-scale occupation of land resources by construction solid waste and industrial solid waste, and reduced the pollution of the environment by waste. DETAILED DESCRIPTION

[0037] The present invention is further described in detail in the following examples. It should be noted that the following examples are intended to facilitate the understanding of the present invention and do not have any limiting effect on the present invention.

[0038] Example 1

[0039] A low-carbon and high-strength building recycled micropowder compounded red mud cementitious material comprises the following components in parts by mass: 40 parts of ultrafine red mud powder, 30 parts of building recycled micropowder, and 5 parts of a reinforcing agent.

[0040] Ultrafine red mud powder is composed of graded nano powder, and the passing rate and mass fraction of each particle size are as follows:

[0041] 100 mesh-200 mesh: 90%; 200 mesh-500 mesh: 70%; 500 mesh-1000 mesh: 50%; 1000 mesh-3000 mesh: 30%; 3000 mesh-5000 mesh: 10%.

[0042] The building recycled micro powder is recycled mortar powder, in which the mass fraction of CaO is 27%, the mass fraction of SiO2 is 38%, and the mass fraction of Al2O3 is 24%.

[0043] The reinforcing agent is composed of a superplasticizer, a penetrant and an activator, and its mass parts are as follows: 2 parts of superplasticizer; 1 part of penetrant; 2 parts of activator.

[0044] The superplasticizer is a mixture of polycarboxylate and acrylic resin, which is compounded in a mass ratio of 1:1.

[0045] The penetrant is silicate.

[0046] The activator is a mixture of nano sodium silicate, nano sodium hydroxide and calcium oxide, which is compounded in a mass ratio of 1:1.5:1.2.

[0047] The preparation method of the low-carbon high-strength building recycled micropowder compounded with red mud cementitious material comprises the following steps:

[0048] ① Dry and dispose red mud and construction solid waste separately to obtain a water content of 0.15wt%;

[0049] ② Preparation of ultra-fine red mud powder: Grind the red mud with a gas colloid mill, and prepare 100-200 mesh, 200-500 mesh, 500-1000 mesh, 1000-3000 mesh, 3000-5000 mesh nano red mud powder according to the grinding time, and prepare graded nano powder according to the following ratios: 100-200 mesh: 90%; 200-500 mesh: 70%; 500-1000 mesh: 50%; 1000-3000 mesh: 30%; 3000-5000 mesh: 10%;

[0050] ③ Preparation of construction recycled micro powder: Grind the construction solid waste with a gas phase colloid mill to obtain recycled mortar powder with a passing rate of 0.075 mm and a passing rate of 90%;

[0051] ④Prepare the reinforcing agent: put 2 parts of superplasticizer, 1 part of penetrant and 2 parts of activator into a mixing tank at the same time, stir for 5 minutes at a stirring rate of 100 rpm.

[0052] ⑤ Preparation of low-carbon and high-strength building recycled micropowder compounded red mud cementitious material: first mix 40 parts of ultrafine red mud powder with 5 parts of enhancer, stir in a mixing pot for 5 minutes, then add 30 parts of building recycled micropowder and stir for 5 minutes to obtain a uniform low-carbon and high-strength building recycled micropowder compounded red mud cementitious material.

[0053] Example 2

[0054] A low-carbon high-strength building recycled micropowder compounded red mud cementitious material comprises the following components in parts by mass: 55 parts of ultrafine red mud powder; 38 parts of building recycled micropowder; and 7 parts of a reinforcing agent.

[0055] The ultrafine red mud powder is composed of graded nano powder, and the pass rate and mass fraction of each particle size are as follows: 100 mesh-200 mesh: 96%; 200 mesh-500 mesh: 78%; 500 mesh-1000 mesh: 57%; 1000 mesh-3000 mesh: 38%; 3000 mesh-5000 mesh: 22%.

[0056] The building recycled micro powder is a combination of recycled mortar powder and recycled red brick powder, in which the mass fraction of CaO is 30%, the mass fraction of SiO2 is 34%, and the mass fraction of Al2O3 is 24%.

[0057] The reinforcing agent is composed of a superplasticizer, a penetrant and an activator, and the weight proportions thereof are as follows: 5 parts of superplasticizer; 1 part of penetrant; and 1 part of activator.

[0058] The superplasticizer is a mixture of polycarboxylate, aminosulfonate and acrylic resin, which is compounded in a mass ratio of 1:1:1.5.

[0059] The penetrant is a mixture of silicate and calcium chloride, which is compounded in a mass ratio of 1:1.

[0060] The activator is a mixture of nano sodium silicate and nano sodium hydroxide, which is compounded in a mass ratio of 1:2.

[0061] The preparation method of the low-carbon high-strength building recycled micropowder compounded with red mud cementitious material comprises the following steps:

[0062] ① Dry and dispose red mud and construction solid waste separately to obtain a water content of 0.1wt%;

[0063] ② Preparation of ultrafine red mud powder: Grinding the red mud with a gas colloid mill, preparing 100-200 mesh, 200-500 mesh, 500-1000 mesh, 1000-3000 mesh, 3000-5000 mesh nano red mud powder according to the grinding time, and preparing graded nano powder according to the proportions of 100-200 mesh: 96%; 200-500 mesh: 78%; 500-1000 mesh: 57%; 1000-3000 mesh: 38%; 3000-5000 mesh: 22%;

[0064] ③ Preparation of building recycled micro powder: Grind the building solid waste with a gas phase colloid mill to obtain recycled mortar powder and recycled red brick powder with a passing rate of 0.075mm and 96%;

[0065] ④Prepare the reinforcing agent: put 5 parts of superplasticizer, 1 part of penetrant and 1 part of activator into the mixing tank at the same time, stir for 6 minutes at a stirring rate of 150 rpm.

[0066] ⑤ Preparation of low-carbon and high-strength building recycled micropowder compounded red mud cementitious material: first mix 55 parts of ultrafine red mud powder with 7 parts of enhancer, stir in a mixing pot for 7 minutes, then add 38 parts of building recycled micropowder, stir for 8 minutes, and you can get a uniform low-carbon and high-strength building recycled micropowder compounded red mud cementitious material.

[0067] Example 3

[0068] A low-carbon high-strength building recycled micropowder compounded red mud cementitious material comprises the following components in parts by mass: 70 parts of ultrafine red mud powder; 60 parts of building recycled micropowder; and 10 parts of a reinforcing agent.

[0069] The ultrafine red mud powder is composed of graded nano powder, and the pass rate and mass fraction of each particle size are as follows: 100 mesh-200 mesh: 100%; 200 mesh-500 mesh: 80%; 500 mesh-1000 mesh: 70%; 1000 mesh-3000 mesh: 50%; 3000 mesh-5000 mesh: 30%.

[0070] The building recycled micro powder is recycled mortar powder, and the CaO mass fraction of the recycled mortar powder is 35%, the SiO2 mass fraction is 36%, and the Al2O3 mass fraction is 23%.

[0071] The reinforcing agent is composed of a superplasticizer, a penetrant and an activator, and its mass parts are as follows: 2 parts of superplasticizer; 3 parts of penetrant; 5 parts of activator.

[0072] The superplasticizer is a mixture of polycarboxylate, aminosulfonate and acrylic resin, which are compounded in a mass ratio of 1:1:2;

[0073] The penetrant is a mixture of silicate, calcium chloride and nano-magnesium fluorosilicate, compounded in a mass ratio of 1:2:3;

[0074] The activator is a mixture of nano sodium silicate and nano sodium hydroxide, which is compounded in a mass ratio of 1:1.

[0075] The preparation method of the low-carbon high-strength building recycled micropowder compounded with red mud cementitious material comprises the following steps:

[0076] ① Dry the red mud and construction solid waste to a water content of 0.05wt%;

[0077] ② Preparation of ultrafine red mud powder: Grinding the red mud with a gas colloid mill, preparing nano red mud powders of 100-200 mesh, 200-500 mesh, 500-1000 mesh, 1000-3000 mesh, and 3000-5000 mesh respectively according to the grinding time, and preparing graded nano powders according to the ratios of 100-200 mesh: 100%; 200-500 mesh: 80%; 500-1000 mesh: 70%; 1000-3000 mesh: 50%; 3000-5000 mesh: 30%;

[0078] ③ Preparation of construction recycled micro powder: Grind the construction solid waste with a gas phase colloid mill to obtain recycled mortar powder with a passing rate of 0.075mm and 98%;

[0079] ④ Preparation of reinforcing agent: Add 2 parts of superplasticizer, 3 parts of penetrant and 5 parts of activator into a mixing tank at the same time, stir for 8 minutes at a stirring rate of 200 rpm to obtain the reinforcing agent;

[0080] ⑤ Preparation of low-carbon and high-strength building recycled micropowder compounded red mud cementitious material: first mix 70 parts of ultrafine red mud powder with 10 parts of enhancer, stir in a mixing pot for 10 minutes, then add 60 parts of building recycled micropowder and stir for 10 minutes to obtain a uniform low-carbon and high-strength building recycled micropowder compounded red mud cementitious material.

[0081] Example 4

[0082] A low-carbon and high-strength building recycled micropowder compounded red mud cementitious material comprises the following components in parts by mass: 48 parts of ultrafine red mud powder; 52 parts of building recycled micropowder; and 8 parts of a reinforcing agent.

[0083] The ultrafine red mud powder is composed of graded nano powder, and the pass rate and mass fraction of each particle size are as follows: 100 mesh-200 mesh: 100%; 200 mesh-500 mesh: 74%; 500 mesh-1000 mesh: 52%; 1000 mesh-3000 mesh: 46%; 3000 mesh-5000 mesh: 26%.

[0084] The building recycled micro powder is recycled mortar powder, and the CaO mass fraction of the recycled mortar powder is 35%, the SiO2 mass fraction is 36%, and the Al2O3 mass fraction is 23%.

[0085] The reinforcing agent is composed of a superplasticizer, a penetrant and an activator, and its mass parts are as follows: 4 parts of superplasticizer; 2 parts of penetrant; 2 parts of activator.

[0086] The superplasticizer is a mixture of polycarboxylate, aminosulfonate and acrylic resin, which are compounded in a mass ratio of 1:1:3;

[0087] The penetrant is a mixture of silicate, calcium chloride and nano-magnesium fluorosilicate, compounded in a mass ratio of 1:2:1;

[0088] The activator is a mixture of nano sodium silicate and nano sodium hydroxide, which is compounded in a mass ratio of 1:2.

[0089] The preparation method of the low-carbon high-strength building recycled micropowder compounded with red mud cementitious material comprises the following steps:

[0090] ① Dry the red mud and construction solid waste to a water content of 0.08wt%;

[0091] ② Preparation of ultrafine red mud powder: Grinding the red mud with a gas colloid mill, preparing nano red mud powders of 100-200 mesh, 200-500 mesh, 500-1000 mesh, 1000-3000 mesh, and 3000-5000 mesh respectively according to the grinding time, and preparing graded nano powders according to the ratios of 100-200 mesh: 100%; 200-500 mesh: 74%; 500-1000 mesh: 52%; 1000-3000 mesh: 46%; 3000-5000 mesh: 26%;

[0092] ③ Preparation of construction recycled micro powder: Grind the construction solid waste with a gas phase colloid mill to obtain recycled mortar powder with a passing rate of 0.075 mm and a passing rate of 95%;

[0093] ④ Preparation of reinforcing agent: Add 4 parts of superplasticizer, 2 parts of penetrant and 2 parts of activator into a mixing tank at the same time, stir for 8 minutes at a stirring rate of 200 rpm to obtain the reinforcing agent;

[0094] ⑤ Preparation of low-carbon and high-strength building recycled micropowder compounded red mud cementitious material: first mix 48 parts of ultrafine red mud powder with 8 parts of enhancer, stir in a mixing pot for 10 minutes, then add 52 parts of building recycled micropowder and stir for 10 minutes to obtain a uniform low-carbon and high-strength building recycled micropowder compounded red mud cementitious material.

[0095] In order to test the performance of building recycled micropowder compounded red mud cementitious materials, the mortar was prepared according to the water-cement ratio of 0.25, and the rectangular specimens were cast to test their compressive strength, flexural strength and shrinkage coefficient. The results are shown in Table 1.

[0096] Table 1 Performance test results of building recycled micropowder compounded red mud cementitious materials

[0097]

[0098] It can be found that the prepared building recycled micropowder compounded red mud cementitious material has excellent properties, fast strength growth, a 7d compressive strength of up to 52.2MPa, and a 28d compressive strength of up to 60MPa, and has high-strength characteristics; in addition, the building recycled micropowder compounded red mud cementitious material of the present invention is prepared from construction solid waste materials, which greatly reduces the pollution of construction solid waste materials to the environment. At the same time, it does not require high-temperature calcination, and belongs to a low-carbon production technology with significant economic, social and environmental benefits.

[0099] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A low-carbon, high-strength building recycled micropowder compounded red mud cementitious material, characterized in that: The composition includes the following components in parts by weight: Ultrafine red mud powder: 40-70 parts; Building recycled micro powder: 30-60 parts; Enhancer: 5-10 parts; The ultrafine red mud powder and the building recycled micro powder are gas-phase ground, and the mixture is evenly stirred with a reinforcing agent to obtain a low-carbon and high-strength building recycled micro powder-compounded red mud cementitious material.

2. The low-carbon high-strength building recycled micropowder compounded red mud cementitious material according to claim 1, characterized in that: The ultrafine red mud powder is composed of graded nano powder, and the passing rate and mass fraction of each particle size are as follows: 100 mesh-200 mesh: 90%-100%; 200 mesh-500 mesh: 70%-80%; 500 mesh-1000 mesh: 50%-70%; 1000 mesh-3000 mesh: 30%-50%; 3000 mesh-5000 mesh: 10%-30%.

3. The low-carbon high-strength building recycled micropowder compounded red mud cementitious material according to claim 1 is characterized by: The construction recycled micro powder is one or a combination of recycled mortar powder and recycled red brick powder; the fineness of the construction recycled micro powder meets the requirement of 0.075mm with a passing rate of more than 90%.

4. The low-carbon high-strength building recycled micropowder compounded red mud cementitious material according to claim 3 is characterized by: The mass fraction of CaO in the building recycled micro-powder is greater than 25%, the mass fraction of SiO2 is greater than 30%, and the mass fraction of Al2O3 is greater than 20%.

5. The low-carbon high-strength building recycled micropowder compounded red mud cementitious material according to claim 1 is characterized by: The reinforcing agent comprises a superplasticizer, a penetrant and an activator, and the mass fractions thereof are as follows: Superplasticizer: 2-5 parts; Penetrant: 1-3 parts; Activator: 1-5 parts.

6. The low-carbon high-strength building recycled micropowder compounded red mud cementitious material according to claim 5 is characterized by: The superplasticizer is one or more of polycarboxylate, aminosulfonate and acrylic resin.

7. The low-carbon high-strength building recycled micropowder compounded red mud cementitious material according to claim 5 is characterized by: The penetrant is one or more of silicate, calcium chloride and nano magnesium fluorosilicate.

8. The low-carbon high-strength building recycled micropowder compounded red mud cementitious material according to claim 5, characterized in that: The activator is one or more of nano sodium silicate, nano sodium hydroxide and calcium oxide.

9. The method for preparing the low-carbon high-strength building recycled micropowder compounded red mud cementitious material according to claim 1, characterized in that: The following steps are involved: S1. Dry the red mud and construction solid waste separately, and the water content is required to be no more than 0.2wt%; S2. Preparation of ultrafine red mud powder: Grinding red mud with a gas colloid mill, preparing graded nanopowders with particle size pass rates and mass fractions of 100 mesh-200 mesh: 90%-100%, 200 mesh-500 mesh: 70%-80%, 500 mesh-1000 mesh: 50%-70%, 1000 mesh-3000 mesh: 30%-50%, 3000 mesh-5000 mesh: 10%-30% respectively according to the grinding time; S3. Preparation of recycled building powder: Grinding construction solid waste by gas colloid mill to obtain recycled mortar powder and / or recycled red brick powder with a pass rate of more than 90% at 0.075mm; S4. Preparation of enhancer: 2-5 parts of superplasticizer, 1-3 parts of penetrant and 2-5 parts of activator are simultaneously added to a mixing tank and stirred for 5-8 minutes at a stirring rate of 100-200 rpm; S5. Preparation of low-carbon and high-strength building recycled micropowder compounded red mud cementitious material: first mix 40-70 parts of ultrafine red mud powder with 5-10 parts of reinforcing agent, stir in a mixing pot for 5-10 minutes, then add 30-60 parts of building recycled micropowder, stir for 5-10 minutes, and you can get a uniform low-carbon and high-strength building recycled micropowder compounded red mud cementitious material.